Food waste management and green purchasing behaviour among youths in Malaysia - Mohamed Zain, Izzah Nadhirah; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Malaysia still produces an estimated around 37,890 tonnes of waste per day and 16,687 tonnes of it is food waste in 2019. This figure gives the impression that Malaysians are still not trying to reduce waste as higher amount of waste can reflect the quantity purchased by Malaysians. This situation occurs because it has become a habit to purchase items that cannot be recycled or reused without feeling bad for the environment. The aims of this paper are to highlight the issues and strategies in food waste reduction in Malaysia. Secondary data are collected regarding “food waste”, “waste management” and “environment friendly food purchasing” scope matters. There are several categories of food waste in Malaysia, food losses from production in the food supply chain, unavoidable, and avoidable food waste. Food waste does affect the environment through the greenhouse gas emissions, climate change, land occupation footprint and water footprint. The strategies to overcome the problem of food waste disposals in Malaysia are through composting, recycling, and anaerobic digestion treatment. Green purchasing is an influential driver in almost all the beginning movement of sustainability in the supply chain, which also included food processing until the disposal phase.